Kaji Numerik Pengaruh Bio-Based Lubricant Terhadap Ketebalan Lapisan Film Dan Tekanan Elastohydrodynamic Pada Cylindrical Roller Bearing Menggunakan Metode Beda Hingga - Adibyathul Fikri Januar; Dedi Rosa Putra Cupu; Nazaruddin Nazaruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
In this research, numerical study are used to examine the effect of bio-based lubricants, i.e. coconut oil, olive oil, and palm oil as lubricants in the application of roller element bearings, or called elastohydrodynamic lubrication (EHL), especially in contact with the inner ring with cylindrical roller elements. This simulation applies the finite difference method to solve the Reynolds equation and the pressure-viscosity equation to analyze the EHL pressure and the thickness of the film layer formed. The results show that olive oil is the right choice in replacing mineral oil in the application of roller bearings. By providing variations in load and speed, olive oil shows the results of low pressure spikes or no pressure spikes during the simulation process. However, in general coconut oil and palm oil can replace mineral oil as a function of lubrication. As a comparison purpose, mineral oil (P150N) is used to see the difference that occurs in the EHL pressure and the thickness of the film layer formed. Keywords: elastohydrodynamic lubrication, film thickness, bio-based lubricant